If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X = -39 + x Solving X = -39 + x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Simplifying X = -39 + x
| 12y-10=20 | | 11x^3=704 | | 6y-8w= | | 0=-24-x^2+11x | | 8x-4+100=180 | | 18p+15=21 | | 7x+7=13-2x | | -3(-7+8r)= | | 7b(b+2)+b=0 | | 9(-6n+8)-4(11-12n)=-9n+3n | | 8x-4+100= | | 2x+1=6x | | 9(x-3)=-(2x+4) | | X+21=x-18 | | 42+x=43x | | r^2-8r=48 | | (8a-3)-(a+2)= | | 3x^3-36y= | | 5(m+9)=-5 | | 4u-8=20 | | C=120*3.14 | | 5x^2+12-2=0 | | -7x+12=-5x-28 | | n^3+-8n^2-n+8=0 | | 8x+1=10x | | 4x^2-15x+10=2x+6 | | 51=3v+9 | | 7cos(2x)+1=0 | | -(-4z^2+z-5)= | | 5w^2=35 | | (4a)(2b)= | | -(5(a+1))=9-(5-(2a-3)) |